The Intestinal Fate of Citrus Flavanones and Their Effects on Gastrointestinal Health - Stevens, Yala; Rymenant, Evelien Van; Grootaert, Charlotte; Camp, John Van; Possemiers, Sam; Masclee, Adrian; Jonkers, Daisy (Nutrients, 2019)
Citrus flavanones, with hesperidin and naringin as the most abundant representatives, have various beneficial effects, including anti-oxidative and anti-inflammatory activities. Evidence also indicates that they may impact the intestinal microbiome and are metabolized by the microbiota as well, thereby affecting their bioavailability. In this review, we provide an overview on the current evidence on the intestinal fate of hesperidin and naringin, their interaction with the gut microbiota, and their effects on intestinal barrier function and intestinal inflammation. These topics will be discussed as they may contribute to gastrointestinal health in various diseases. Evidence shows that hesperidin and naringin are metabolized by intestinal bacteria, mainly in the (proximal) colon, resulting in the formation of their aglycones hesperetin and naringenin and various smaller phenolics. Studies have also shown that citrus flavanones and their metabolites are able to influence the microbiota composition and activity and exert beneficial effects on intestinal barrier function and gastrointestinal inflammation. Although the exact underlying mechanisms of action are not completely clear and more research in human subjects is needed, evidence so far suggests that citrus flavanones as well as their metabolites have the potential to contribute to improved gastrointestinal function and health.